Women in the Church of God in Christ : Making a Sanctified World - Butler, Anthea D., 1960- (Book collections on Project MUSE., 2007)
The Church of God in Christ (COGIC), an African American Pentecostal denomination founded in 1896, has become the largest Pentecostal denomination in the United States today. In this first major study of the church, Anthea Butler examines the religious and social lives of the women in the COGIC Women's Department from its founding in 1911 through the mid-1960s. She finds that the sanctification, or spiritual purity, that these women sought earned them social power both in the church and in the black community. --from publisher description.